AB1464-HPR Development of a musculoskeletal ultrasound evaluation and reporting tool. (23rd January 2014) - Dobrica, C.; Lovegrove, F.; Cullinane, S.; McLaren, J.; Harris, H.; Gibson, J.
Abstract : Background: MSUS is used in our Department by all Consultant Rheumatologists at early RA and review Rheumatology Clinics but is not used by the Rheumatology Nurse Practitioner (RNP) who sees RA review patients. In order to provide MSUS during the RNP review clinic, a Rheumatology Specialist Physiotherapist/Sonographer (RSPS) was allocated to scan all patients immediately prior to attendance with the RNP. To ensure that the findings of the MSUS were accurately documented and interpreted, an evaluation tool needed to be developed. Objectives: 1) To determine the rate of inter-reader reliability of the tool. 2) To determine whether use of the new tool is time-efficient Methods: A series of graphical forms reflecting MSUS standard examination were designed and subsequently trialled by all MSUS practitioners, resulting in the final format. Scoring was graded 0 to 3 according to EULAR, OMERACT scoring for synovitis, and synovial hypertrophy. The erosions were recorded for presence and position. Each joint was graphically represented as a box containing the appropriate MSUS image with a tick-box system for grading synovial hypertrophy, synovitis, and presence of erosions (see Image 1). The RNP was trained to interpret the new form and inter-observer variability was reviewed in clinics between September 2011 and January 2012 for 100 consecutive patients. Results: The Inter-reader reliability for the form was 100%. The time required to document and report the MSUS findings was 1 minute. Previous handwritten reports took 5 minutes. For a clinic with 10 patients, using the new form can save up to 40 minutes. Conclusions: The use of our MSUS graphical tick-box tool ensured 100% inter-reader reliability between the RNP and the RSPS. Provision of one-stop reports of the MSUS findings allows the RNP to base clinical decisions on presence or absence of US detected synovitis and erosions.It is fast to complete and read, thus saving time in clinic. Disclosure of Interest: None Declared